Burden and quality of life of mothers of children and adolescents with chronic illnesses: an integrative review - Macedo, Eliza Cristina (Escola de Enfermagem de Ribeirão Preto / Universidade de São Paulo, 2015)

(untitled) (Rev Lat Am Enfermagem)
OBJECTIVE: to identify and analyze the evidence available regarding evaluation of burden and quality of life of mothers who are caregivers for children and adolescents with chronic illnesses. METHOD: an integrative review, undertaken in the electronic sources MEDLINE; Academic Search Premier; CINAHL; LILACS; SciELO and PubMed, between 2010 and 2014. RESULTS: among the 22 documents selected, there was a predominance of convenience samples and non-experimental transversal designs, at the levels IV and III2. The caregiver burden scales used were the Zarit Burden Interview and Montgomery-Borgatta Caregiver Burden Scale-Revised along with the following instruments for evaluating quality of life: The World Health Organization Quality of Life-BREF Scale; Self-report questionnaires; The Ulm Quality of Life Inventory for Parents of chronically ill children; Asthma Caregiver Quality of Life Questionnaire; and the Nottingham Health Profile. Quality-of-life appears to be influenced in a complex and interrelated way by the physical and mental health of the mothers who are caregivers, in accordance with their level of independence, social relationships, environment, and the extent to which they see themselves as burdened. CONCLUSION: the revealing of the results for the evaluation of burden and quality of life of mothers who are caregivers has implications for the planning and implementation of effective interventions, by the multidisciplinary team, if they are to relieve the burden.